Splitting the sḏm.n⸗f? A Discussion of Written Forms in Coffin Texts: Part 2 - Stauder, Andréas (Zeitschrift für ägyptische Sprache und Altertumskunde, 2014)
The paper discusses the written forms of II.red in Coffin Texts adduced by Wolfgang Schenkel in support of his hypothesis of two morphologically distinct forms of the sḏm.n⸗f . Also examined are the case of ult.n non-II.red , which had only a secondary role in Schenkel’s original proposal, and the case of the high-frequency verb wnn , which is special. The conclusion is that none of these written forms supports the hypothesis of two distinct forms of the sḏm.n⸗f , just as none contradicts it. In the course of the argument, various issues of broader interest are touched upon: the representation of verbal morphology in writing, the individual verbs (notably ngigi/ngg “cackle,” originally a N-stem based on an onomatopoietic segment), the morphology of wnn , and aspects of the dynamics of textual variation in Coffin Texts (notably the extraordinarily complex case afforded by CT I 73c–74f; Spell 24).